1990
DOI: 10.1021/bi00487a028
|View full text |Cite
|
Sign up to set email alerts
|

Study of the binding of single-stranded DNA-binding protein to DNA and poly(rA) using electric field induced birefringence and circular dichroism spectroscopy

Abstract: Binding of the single-stranded DNA-binding protein (SSB) of Escherichia coli to single-stranded (ss) polynucleotides produces characteristic changes in the absorbance (OD) and circular dichroism (CD) spectra of the polynucleotides. By use of these techniques, complexes of SSB protein and poly(rA) were shown to display two of the binding modes reported by Lohman and Overman [Lohman, T.M., & Overman, L. (1985) J. Biol. Chem. 260, 3594-3603]. The circular dichroism spectra of the "low salt" (10 mM NaCl) and "high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

1992
1992
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 40 publications
1
7
0
Order By: Relevance
“…Using Raman spectroscopy, Otto et al (1988) observed increased hyperchromicities upon binding of either Ml3 gene V or T4 gene 32 proteins to poly (dA) but not to poly (A). As mentioned above, Kuil et al (1990) have shown using electric field induced birefringence that the bases in poly(dA) become partially unstacked upon binding E. coli SSB protein, and similar observations have been made for T4 gene 32 protein (Scheerhagen et al, 1985;van Amerongen et al, 1988). If coupling of base unstacking to protein-DNA binding provides the explanation for the nonlinear van't Hoff plots observed for the E. coli SSB tetramer-dA(pA)" binding, then nonlinear van't Hoff plots with ACp < 0 should also be observed for binding of poly(dA) to the T4 gene 32 protein, the fl gene V protein, and possibly other SSB proteins.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…Using Raman spectroscopy, Otto et al (1988) observed increased hyperchromicities upon binding of either Ml3 gene V or T4 gene 32 proteins to poly (dA) but not to poly (A). As mentioned above, Kuil et al (1990) have shown using electric field induced birefringence that the bases in poly(dA) become partially unstacked upon binding E. coli SSB protein, and similar observations have been made for T4 gene 32 protein (Scheerhagen et al, 1985;van Amerongen et al, 1988). If coupling of base unstacking to protein-DNA binding provides the explanation for the nonlinear van't Hoff plots observed for the E. coli SSB tetramer-dA(pA)" binding, then nonlinear van't Hoff plots with ACp < 0 should also be observed for binding of poly(dA) to the T4 gene 32 protein, the fl gene V protein, and possibly other SSB proteins.…”
Section: Discussionmentioning
confidence: 83%
“…Electric field induced birefringence and circular dichroism studies indicate that the bases in poly(A) become unstacked, at least partially, upon binding E. coli SSB protein (Kuil et al, 1990). On the other hand, since the bases within free dT(pT)" or dC(pC)" are not stacked significantly, similar base unstacking should not occur upon SSB binding to dT(pT)" or dC(pC)".…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The first is that SSB/protein interactions could have important, but previously unrecognized, roles protein translation. Indeed, SSBs from E. coli and bacteriophage are known to bind single-stranded RNA in a manner that influences translation [45][47] [48], [49]. Moreover, proteomic studies have shown that SSB from both E. coli and B. subtilis associate with ribosomal subunits [43], [50], although, due to the prevalence of ribosomal proteins as common contaminants in proteome-wide studies, the possibility that these are bona fide interactions has not be pursued further.…”
Section: Discussionmentioning
confidence: 99%
“…velocity (Lohman & Overman, 1985; Lohman et al, 1986; Bujalowski & Lohman, 1986;Bujalowski et al, 1988), and circular dichroism (Kuil et al, 1990). In complexes with poly(dT) at 25 °C, pH 8.1, the SSB tetramer can form three of these modes with = 35, 56, or 65 nucleotides per tetramer.…”
mentioning
confidence: 99%